2021
DOI: 10.1021/acs.jcim.1c00594
|View full text |Cite
|
Sign up to set email alerts
|

Spodium Bonds in Biological Systems: Expanding the Role of Zn in Protein Structure and Function

Abstract: Understanding the structural and functional implications of metal ions is of pivotal significance to chemical biology. Herein, we report first time the evidence of spodium bonds (SpB’s, an attractive noncovalent force involving elements from group 12 and electron-rich species) in tetrahedral Zn-binding sites. Through a combined crystallographic (PDB analysis) and computational ( ab initio calculations) study, we demonstrate that Zn SpB’s are abundant and might be involved in protein stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 62 publications
(78 reference statements)
2
24
0
Order By: Relevance
“…In general, Chemistry-A European Journal there is a good correlation between the WfB distances and the values of 1 (the shorter the distance the greater the 1) in line with previous investigations. [8][9][10] Apart from complexes 6-8, 11, 15 and 19, that exhibit equilibrium distances slightly below the sum of the covalent radii, the values of 1 at the BCP are similar to those reported for noncovalent interactions involving elements of groups 7 [8] and 8. [9] Concluding Remarks…”
Section: Chemistry-a European Journalsupporting
confidence: 77%
See 1 more Smart Citation
“…In general, Chemistry-A European Journal there is a good correlation between the WfB distances and the values of 1 (the shorter the distance the greater the 1) in line with previous investigations. [8][9][10] Apart from complexes 6-8, 11, 15 and 19, that exhibit equilibrium distances slightly below the sum of the covalent radii, the values of 1 at the BCP are similar to those reported for noncovalent interactions involving elements of groups 7 [8] and 8. [9] Concluding Remarks…”
Section: Chemistry-a European Journalsupporting
confidence: 77%
“…Similarly to RgBs and SpBs, which have been characterized in a biological context, [10] we report evidence of this novel NCI in the context of Mo and W enzymatic chemistry by combining a search in the Protein Data Bank (PDB) [11] with an ab initio study at the RI-MP2/def2-TZVP level of theory to further demonstrate the existence and favorable nature of the interaction.…”
mentioning
confidence: 86%
“…A more detailed PDB survey by Biswal et al ascertained the presence of Sp-bonds in a biological system, where they found that approximately 70% of the interactions are from amino acid residues, 20% from water, and 10% from the coordinated ligands. 174 They investigated two systems to quantify the strength and impact of this interaction in proteins. One of the systems is a class of metalloproteins that involves the cleavage of peptide bonds.…”
Section: Recent Discoveriesmentioning
confidence: 99%
“…halogen or pnicogen bond. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] These prior studies have shown than an important component of the bonding arises from a depletion of electron density in a limited region surrounding this central atom, whose positive charge attracts a nucleophile. In a common situation, this density depletion occurs along the antipode of an R-X covalent σ-bond (where X refers to the central atom), and so is termed a σ-hole.…”
Section: Introductionmentioning
confidence: 99%
“…The ensuing interaction is typically named after the family of the periodic table from which this atom is derived, e.g. halogen or pnicogen bond 6–22 . These prior studies have shown than an important component of the bonding arises from a depletion of electron density in a limited region surrounding this central atom, whose positive charge attracts a nucleophile.…”
Section: Introductionmentioning
confidence: 99%